SURVEI SARANA DAN PRASARANA PENDIDIKAN JASMANI DAN OLAHRAGA DI SMP NEGERI SE-DISTRIK KUALA KENCANA KABUPATEN MIMIKA - Marianus Nong Reni (SATRIA : Journal of Sports Athleticism in Teaching and Recreation on Interdisciplinary Analysis, 2022)
This research is motivated by the still limited facilities and infrastructure for Junior High School Physical Education in the Kuala Kencana district, Mimika Regency.This study aims to determine the state of the physical education facilities and infrastructure for public junior high schools in the district of Kuala Kencana, Mimika Regency.This research is a descriptive research with survey method.The data collection technique is direct observation in the field and the data results are entered into the observation sheet.The population of this study is a public junior high school in the district of Kuala Kencana, Mimika Regency, which consists of 3 schools.All schools are used as research objects so that this research can be stated as a population study.Based on research on a survey of physical education facilities and infrastructure for public junior high schools in Kuala Kencana District, Mimika Regency, it was concluded that the good category was 1 school (33.33%), the medium category was 1 school (33.33%), the less category was 1 school.